Enhancing Care for Individuals with Mobility Impairments: Lessons Learned in the Implementation of a Primary Care–Based Mobility Clinic - Joseph Lee, James Milligan, Loretta M. Hillier and Colleen McMillan (Healthcare Quarterly, 2013)
Persons with mobility impairments experience significant barriers to primary healthcare. This study examines key lessons learned, as derived from interviews with referral sources and Centre for Family Medicine Mobility Clinic team members, in the development and implementation of a primary care–based mobility clinic aimed at reducing these barriers, and it reflects on the implications of this model of care on the system of care. Results highlight the importance of accessibility, specialized equipment, promotional activities and management support as well as challenges reflected by system barriers to care. The results of this study have implications for the application of this model of care in other settings.
Keywords: access, health services, mobility impairments, disabilities, primary care